2018
DOI: 10.1016/j.neuropsychologia.2017.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The life stories of adults with amnesia: Insights into the contribution of the medial temporal lobes to the organization of autobiographical memory

Abstract: Autobiographical memories are not stored in isolation but rather are organized into life chapters, higher-order knowledge structures that represent major themes conveying the arc of one's life. Neuropsychological studies have revealed that both episodic memory and some aspects of personal semantic memory are impaired in adults with medial temporal lobe (MTL) damage. However, whether such impairment compromises the retrieval and formation of life chapters is unknown. Therefore, we had 10 adults with MTL amnesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
2

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Also, given that our EAM assessment can be assumed to place relatively high demands on narrative ability and working memory, consistent with prior work (Grilli & Verfaellie, 2015; Grilli et al, 2018), we administered the subtests that contribute to the Wechsler Adult Intelligence Scale (WAIS-IV; Weschsler, 2008) Verbal Comprehension Index and the Working Memory Index.…”
Section: Methodsmentioning
confidence: 94%
“…Also, given that our EAM assessment can be assumed to place relatively high demands on narrative ability and working memory, consistent with prior work (Grilli & Verfaellie, 2015; Grilli et al, 2018), we administered the subtests that contribute to the Wechsler Adult Intelligence Scale (WAIS-IV; Weschsler, 2008) Verbal Comprehension Index and the Working Memory Index.…”
Section: Methodsmentioning
confidence: 94%
“…There may also be age-of-onset effects in amnesia (Grilli, Wank, & Verfaellie, 2018). Kopelman, Wilson, and Baddeley (1989) found that older, but not younger, patients showed a steep gradient, arguing that: "Older subjects (but not the younger) encode or consolidate new [recent] memories in a way that somehow makes them more vulnerable to the effects of brain damage than our earlier memories."…”
Section: The Temporal Gradient: a Hypothesismentioning
confidence: 99%
“…It is likely that the relationships between autobiographical periods and specific episodes are characterized by many associations so that a given memory could be part of multiple autobiographic periods which themselves could be contained in multiple "Life Chapters" [168,179]. Life chapters are major components in this hierarchical autobiographical knowledge structure that reflect extended time periods, typically spanning months to years, such as an individual's childhood or career [168,179,180]. As with nested hierarchies, one could predict that the AHC would have a functional role in the recollection of broader-scaled life chapters and the PHC would be more involved in recalling finer-grained episodes.…”
Section: Multi-scale Models Of Declarative Memorymentioning
confidence: 99%